Matrix Stiffness Regulates TGFβ1‐Induced αSMA Expression via a G9a‐LATS‐YAP Signaling Cascade - Chinmay S. Sankhe; Jessica L. Sacco; Victoria L. Crunkleton; Malcom Díaz García; Matthew J. Bierowski; David Vidotto Rezende Soares; Jacob A. Karnick; Rachel L. Cecco; Arefeh Abbasi; Joy Kirigo; Thomas K. Wood; Esther W. Gomez (FASEB BioAdvances)
ABSTRACT Extracellular matrix stiffness is enhanced in cancer and fibrosis; however, there is limited knowledge on how matrix mechanics modulate expression and signaling of the methyltransferase G9a. Here, we show that matrix stiffness and transforming growth factor (TGF)‐β1 signaling together regulate G9a expression and the levels of the histone mark H3K9me2. Suppressing the activity and expression of G9a attenuates TGFβ1‐induced alpha smooth muscle actin (αSMA) and N‐cadherin expression and cell morphology changes in mammary epithelial cells cultured on stiff substrata. Knockdown of G9a increases the expression of large tumor suppressor kinase 2 (LATS2) and decreases the nuclear localization of yes associated protein (YAP). Furthermore, inhibition of LATS promotes an increase in YAP nuclear localization and αSMA expression, while inhibition of YAP attenuates αSMA expression. Overall, our findings indicate that a G9a‐LATS‐YAP signaling cascade regulates mammary epithelial cell response to matrix stiffness and TGFβ1.